2016
DOI: 10.1007/978-3-319-47099-3_9
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Overflow Vulnerabilities on GPUs

Abstract: GPU-accelerated computing gains rapidly-growing popularity in many areas such as scientific computing, database systems, and cloud environments. However, there are less investigations on the security implications of concurrently running GPU applications. In this paper, we explore security vulnerabilities of CUDA from multiple dimensions. In particular, we first present a study on GPU stack, and reveal that stack overflow of CUDA can affect the execution of other threads by manipulating different memory spaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Di et al [32] study buffer overflow vulnerabilities in CUDA-based GPUs. By causing a stack overflow, the address of a function pointer can be changed.…”
Section: Buffer Overflow Attackmentioning
confidence: 99%
See 2 more Smart Citations
“…Di et al [32] study buffer overflow vulnerabilities in CUDA-based GPUs. By causing a stack overflow, the address of a function pointer can be changed.…”
Section: Buffer Overflow Attackmentioning
confidence: 99%
“…Clearly, the GPUs from all major vendors are vulnerable to attacks. [20,31,32] Denial of service [12,33] GPU components Global memory information leakage [16,17,23,29,[34][35][36], side-channel [8,26], covert channel [15], buffer overflow [20,32] Shared memory information-leakage [16,17,29,34,36], side-channel [25,26], covert channel [15], buffer overflow […”
Section: A Classification Of Research Workmentioning
confidence: 99%
See 1 more Smart Citation
“…By running a malicious gadget code on an altered control flow path, attackers can collect sensitive data or escalate the attacker's privilege to the system administrator. Recent work has shown that GPUs are also vulnerable to buffer overflow attacks [12,14,47]. For example, research by Miele [45] describes GPU attack scenarios in which the attacker manipulates the function pointer by using a buffer overflow and successfully forces the GPU kernel to execute the malicious function.…”
Section: Introductionmentioning
confidence: 99%
“…GPU executes program in a Single-Instruction, Multiple-Thread (SIMT) fashion, so it is well suited for cryptographic applications deployed in cloud computing environment to provide the Securityas-a-Service (SECaaS). Unfortunately, GPU-based applications are vulnerable to many known attacks as proposed in Di et al (2016); Naghibijouybari et al (2018); Jiang et al (2016). Among those published vulnerabilities *Correspondence: zhouyongbin@iie.ac.cn 1 State Key Laboratory of Information Security, Institute of Information Engineering, Chinese Academy of Sciences, Beijing, China 2 School of Cyber Security, University of Chinese Academy of Sciences, Beijing, China of GPUs, side-channel vulnerabilities are the most serious ones due to their non-invasiveness to target devices.…”
Section: Introductionmentioning
confidence: 99%